Optimization for minimizing the cost of ozonation of highly concentrated textile dyeing wastewater in a bubble column reactor - Chaturvedi A.; Jaiswal R.P. (My University, 2025)
Ozonation is one of the advanced oxidation methods that provide effective decolorization and detoxification of the dyeing wastewater without causing any sludge formation. Despite being a good alternative to biodegradation, ozonation suffers from a high operating cost. This study conducted the ozonation process at high initial dye concentrations and optimized the process parameters (such as initial ozone concentration, initial dye concentration, and pH) to minimize the operating cost in terms of the overall power consumption of the process. The ozonation of Reactive Blue dye was performed in a bubble column reactor at various process conditions. A central composite design (CCD)-based response surface method (RSM) statistical tool was used to optimize the process. An empirical correlation for the specific power consumption (defined as electricity consumed per unit mass of dye removed from a unit volume of dyeing wastewater) was developed and verified. It was found that the specific power consumption during ozonation can be lowered significantly (by ~25–30%) if the dyeing water was treated at high initial dye concentrations. Graphical abstract: [Figure not available: see fulltext.]. © 2022, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.